Spectroscopic Investigation of Chlorin-Based Photosensitizers in Polymer Matrix - Antonina Naumenko; Nataliya Kutsevol (International Journal of Polymer Science)
Chlorin e6 and its derivatives are the basis of a number of drugs used in medicine in the treatment of various diseases, including cancer, by photodynamic therapy. Nonpolar derivatives of Chlorin e6—dimethyl ether of Chlorin e6 (DME Ce6) and trimethyl ether of Chlorin e6 (TME Ce6)—are actively studied for application during photodynamic therapy. In this work, based on the electron optical absorption spectra, the interaction of photosensitizer molecules with branched star-like copolymer dextran-graft-polyacrylamide in anionic form was investigated and the possibility of using the latter as a carrier for drug delivery to tumor cells was suggested.